La paz neoliberal: el postulado de la razón instrumental sobre la razón dialógica - Alvear C., Julio César (2023)
This article is a critique of what I have defined as neoliberal peace, that is, peace based on instrumental reason, understood as the idea of reducing conflicts to a transactional problem. Such an idea implies that people can only find peace if they submit all spheres of their private and their public lives to the laws of supply and demand. Therefore, neoliberalism, by understanding humankind as a means to realize the ends of the market, deepens social inequalities, and thus fosters direct violence, structural violence and cultural violence. To overcome this situation, the article suggests inverting the model and striving for a peace based on dialogical rationality, in other words, a deliberative peace, based on the recognition of the other as an end and not as a means.